DUKUNGAN KESEHATAN JIWA DAN PSIKOSOSIAL (DKJPS) DI MASA PANDEMI COVID-19 SEBAGAI BAKTI NGUDIA UNTUK MADURA - Faisal Amir; Zakkiyatus Zainiyah; Ulva Noviana; M. Hasinuddin (STIKES NGUDIA HUSADA MADURA, 2022)
Severe acute respiratory syndrome corona virus 2 (SARSCOV-2) or more familiarly known as Coronavirus disease 2019 (Covid-19) is a worldwide epidemic that causes chaos in various aspects of life. The impact of COVID-19 is not only felt physically and biologically, but can also have a psycho, social, cultural, economic, political and spiritual impact. In general, the perspective of the Madurese community is divided into two groups, namely people who believe and accept the existence of COVID-19 and people who refuse, do not believe and are ignorant. In the first group, the public really understands well the Covid-19 phenomenon and adheres to prevention protocols and everything related to government programs in preventive efforts. However, in the second group, people have a tendency to distrust the existence of COVID-19 and have low adherence to health protocols. Meanwhile, the special character of the Madurese community is very high obedience, one of which is applied through a philosophy with the term